Development and Current Situation of Special Economic Zones in Kazakhstan (Journal of Economic Research & Business Administration, 2018)
This article has discussed the state regulations of the economy by methods that influence on theeconomy and infrastructural organization, adoption of regulatory legal acts and procedures for controllingfinished works, i.e. conditions for regulation of the national economy. History of special economic zonesin Kazakhstan has been illustrated. The first special economic zone’s history and features of recent SEZ thathave been created during 2001-2013 years have examined. SEZs’ helped to create a good environment forinvestments. SEZs like “Ontustik”, “Astana – new city”, “IT Park”, “Aqtau seaport”, “Burabay”, “Saryarqa”,and “Pavlodar” attracted a lot of investment projects. In this article, similarities of creations of SEZ and theirfunction, their advantages and disadvantages were discussed. During SEZ’s creation history, four significantchanges in Law were adopted. Also, it examined how additions and amendments to normative legal actshelped to improve regulation of special economic zones. In order to contribute effectively to the nationaleconomy, it has been demonstrated how to use special economic zones as an economic tool.